Optimizing of TiN barrier properties for CNT interconnects - Ng, Anthony Tian Shi (2012)
This report aims to investigate the various parameters on optimizing of the Titanium Nitride (TiN) thin films to achieve low resistivity, fabrication of four point probe flip chip design and measurement of the flip chip interconnection resistance. Three controlled parameters are experimented in the process of optimizing of TiN thin films. The first parameter is the nitrogen gas flow rate, followed by the sputtering power parameter and lastly will be the duration of the sputtering time. After optimizing of the TiN thin films, the parameters are used for the contact bump while fabricating of the flip chip interconnection. Last but not least, further investigation of the various contact bump size is also discussed on how it affected the resistance of the interconnection.